Activating solution and activating treatment method of WC powder, activated WC powder and application thereof, and preparation method of WC-Co composite powder

By activate WC powder with specific composition activation liquid and ultrasonic assisted treatment methods, the problems of insufficient toughness of WC materials and high cost of activation methods of precious metals are solved, and the efficient preparation and excellent mechanical properties of WC-Co composite powder are achieved.

CN119663253APending Publication Date: 2025-03-21TAIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411864354.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing WC materials have shortcomings in toughness, and the precious metal activation method is high in cost and has serious environmental pollution. The activation effect of the non-precious metal activation method is not ideal, and the coating quality is unstable.

Method used

An activation solution is provided, which consists of 60-70 vol% nitric acid, 35-45 vol% hydrofluoric acid, ammonium fluoride and water. The WC powder is treated with ultrasonic assisted activation to improve its activity and form a uniform Co plating layer on its surface.

Benefits of technology

High activation of WC powder is achieved, uniform growth of Co plating is promoted, and the mechanical properties of WC-Co composite powder are improved. The obtained WC cemented carbide has excellent hardness and grain size uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663253A_ABST
    Figure CN119663253A_ABST
Patent Text Reader

Abstract

The invention provides an activating solution and an activating treatment method of WC powder, activated WC powder and application thereof, and a preparation method of WC-Co composite powder, and particularly relates to the technical field of surface treatment. The activating solution provided by the invention comprises the following components: 20-60 mL / L of nitric acid with the concentration of 60-70 vol%, 30-50 mL / L of hydrofluoric acid with the concentration of 35-45 vol%, 2-4 g / L of ammonium fluoride and the balance of water. According to the activating solution provided by the invention, by adjusting the content of each component, high activating treatment of the WC powder is realized, so that obvious gully defects are obtained on the surface of the WC powder, and the parts are used as nucleation centers to adsorb foreign substances to form bonds, so that the ceramic powder has high catalytic activity, the contact angle between metal and ceramic interfaces is reduced, and the wettability of WC and metal particles is improved; therefore, uniform growth of a metal coating on the surface of the powder is promoted, and good coating is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment, and in particular relates to an activation liquid and an activation treatment method for WC powder, activated WC powder and application thereof, and a preparation method for WC-Co composite powder. Background Art

[0002] WC material has the high hardness, high temperature resistance and corrosion resistance of ceramics. It is widely used in mining and manufacturing industries. It is known as the "industrial teeth" in the industry, but pure WC has low toughness. It is often sintered with other metals such as nickel, cobalt, copper, etc. to improve toughness. Common composite methods include mechanical alloying, ball milling, chemical plating, etc. However, the composite alloys obtained by mechanical alloying and ball milling have uneven particle size distribution, low reaction activity, and difficult process control. Compared with the other two methods, the WC composite material obtained by chemical plating has the advantages of small particle size, uniform distribution, high reaction activity, etc., and the chemical plating equipment is simple and the process is easy to control.

[0003] The effect of WC activation pretreatment directly affects the coating effect of subsequent chemical plating, and then affects the mechanical properties of the final alloy. The method of using precious metals to activate WC is widely used, but its use cost is high and it causes serious environmental pollution, which is not conducive to sustainable development. Using non-precious metals to activate WC has problems such as unsatisfactory activation effect and unstable coating quality. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide an activation solution and activation treatment method for WC powder, activated WC powder and its application, and a preparation method for WC-Co composite powder. The WC powder activated by the activation solution provided by the present invention has high activity, and when chemical plating is performed on its surface, the coating effect is tight and the plating is uniform; the WC-Co composite powder prepared by using the activated WC powder is sintered to obtain a hard alloy with excellent mechanical properties.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention provides an activation solution, which is composed of: 20-60 mL / L of nitric acid with a concentration of 60-70 vol%, 30-50 mL / L of hydrofluoric acid with a concentration of 35-45 vol%, 2-4 g / L of ammonium fluoride, and the balance of water.

[0007] The present invention also provides the use of the activation liquid described in the above technical solution in activating WC powder.

[0008] The present invention also provides an activation treatment method for WC powder, comprising the following steps:

[0009] The WC powder is preheated, mixed with the activation solution of claim 1 at 50-60° C., and subjected to ultrasonic-assisted activation treatment to obtain activated WC powder.

[0010] Preferably, the ratio of the mass of the WC powder to the volume of the activation solution is 100-500 g:1 L.

[0011] Preferably, the conditions of the ultrasound-assisted activation treatment include: ultrasound power of 300-400 W, ultrasound time of 20-30 min, and ultrasound frequency of 40-60 kHz.

[0012] The present invention also provides an activated WC powder, which is obtained by activating the WC powder by the activation treatment method described in the above technical solution.

[0013] The present invention also provides the use of the activated WC powder described in the above technical solution in preparing a WC composite material by chemical plating.

[0014] The present invention also provides a method for preparing a WC-Co composite powder, comprising the following steps: mixing the activated WC powder according to claim 6 with a Co-containing 2+ The WC-Co composite powder is obtained by mixing the WC-Co composite powder with a chemical plating solution, heating and ultrasonicating the WC powder in sequence to form a Co plating layer on the surface of the WC powder.

[0015] Preferably, the ratio of the mass of the activated WC powder to the volume of the chemical plating solution is 100-200 g:1 L.

[0016] Preferably, the chemical plating solution is composed of: 20-30 g / L cobalt sulfate, 20-30 g / L sodium hypophosphite, 40-60 g / L sodium citrate, 20-30 g / L boric acid, and the balance is water;

[0017] The pH value of the chemical plating solution is 9-11.

[0018] The present invention provides an activation solution, the composition of the activation solution is: 20-60 mL / L of nitric acid with a concentration of 60-70 vol%, 30-50 mL / L of hydrofluoric acid with a concentration of 35-45 vol%, 2-4 g / L of ammonium fluoride, and the balance is water. The activation solution provided by the present invention achieves high activation treatment of WC powder by adjusting the content of each component, so that the surface of the WC powder has obvious gully defects, and these parts will serve as nucleation centers to adsorb foreign substances to form bonds, so that the ceramic powder has high catalytic activity, obtains a larger surface energy, reduces the metal-ceramic interface contact angle, and improves the wettability of WC and Co, thereby promoting the uniform growth of the Co coating on the powder surface and achieving good coating; and the highly activated activation solution can effectively prevent the abnormal growth of WC grains, so that the size of the activated WC powder obtained is uniform.

[0019] The present invention also provides a method for preparing WC-Co composite powder, which uses activated WC powder to chemically plate Co, so that metal particles Co are uniformly deposited on the surface of the WC powder to obtain a coating with uniform thickness.

[0020] The WC hard alloy obtained by sintering the WC-Co composite powder prepared by the invention has a grain size of 0.71-1.24 mu m and a hardness of 2198.3-2708.4 HV. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0022] Figure 1 The SEM images of WC powder after activation in Examples 1 to 5;

[0023] Figure 2 The SEM images of the WC-Co composite powders prepared in Examples 1 to 5;

[0024] Figure 3 The SEM images of WC cemented carbides prepared in Examples 1 to 5;

[0025] Figures 1 to 3 1 to 5 correspond to Examples 1 to 5 respectively.

[0026] Implementation Method

[0027] The invention provides an activation solution, which is composed of: 20-60 mL / L of nitric acid with a concentration of 60-70 vol%, 30-50 mL / L of hydrofluoric acid with a concentration of 35-45 vol%, 2-4 g / L of ammonium fluoride, and the balance of water.

[0028] In the present invention, unless otherwise specified, the raw materials and equipment used are commercially available products well known in the art.

[0029] The activation solution provided by the present invention comprises 20 to 60 mL / L of nitric acid with a concentration of 60 to 70 vol%. In a specific embodiment, the nitric acid content with a concentration of 60 to 70 vol% in the activation solution can be 20 mL / L, 25 mL / L, 30 mL / L, 35 mL / L, 40 mL / L, 45 mL / L, 50 mL / L, 55 mL / L or 60 mL / L; the concentration of the nitric acid can be 60 vol%, 65 vol% or 70 vol%. The nitric acid corrodes the surface of the WC powder particles, so that the surface of the WC powder has obvious gully defects, and these parts will serve as nucleation centers to adsorb foreign substances to form bonds, so that the ceramic powder has high catalytic activity, obtains a larger surface energy, and reduces the metal-ceramic interface contact angle.

[0030] In the present invention, the activation solution includes 30 to 50 mL / L of hydrofluoric acid with a concentration of 35 to 45 vol%. In a specific embodiment, the hydrofluoric acid with a concentration of 35 to 45 vol% in the activation solution can be 30 mL / L, 35 mL / L, 40 mL / L, 45 mL / L or 50 mL / L; the concentration of the hydrofluoric acid can be 35 vol%, 40 vol% or 45 vol%. Hydrofluoric acid acts as a complexing agent to prevent the surface of the WC powder from being excessively corroded by nitric acid and causing body defects.

[0031] In the present invention, the content of ammonium fluoride in the activation solution is 2-4 g / L. In the present invention, the content of ammonium fluoride in the activation solution can be 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L or 4 g / L. Ammonium fluoride provides fluoride ions during the activation process to prevent insufficient complexing ability of the solution.

[0032] In the present invention, the solvent of the activation solution is water.

[0033] The present invention provides the use of the activation liquid described in the above technical solution in activating WC powder.

[0034] The present invention provides an activation treatment method for WC powder, comprising the following steps:

[0035] After preheating the WC powder, the WC powder is mixed with the activation solution of the above technical solution at 50-60° C. and subjected to ultrasonic-assisted activation treatment to obtain activated WC powder.

[0036] Before the preheating, the present invention preferably performs surface pretreatment on the WC powder; the surface pretreatment method preferably includes: placing the WC powder in ethanol for ultrasonic cleaning, washing with water, and drying to obtain the surface pretreated WC powder. The surface pretreatment is used to remove oil stains and impurities on the surface of the WC powder.

[0037] In the present invention, the number of water washing is preferably 2 to 5 times.

[0038] The present invention has no special requirements on the method of ultrasonic cleaning, and the commonly used technical means in the art can be used.

[0039] The present invention has no special requirements on the drying method, and the commonly used technical means in the art can be used, for example, drying.

[0040] In the present invention, the preheating temperature is preferably 50-60° C. In a specific embodiment, the preheating temperature can be 50° C., 55° C. or 60° C. Preheating can prevent the powder temperature from being low, which will cause the activation solution temperature to drop when the activation solution is added, thereby affecting the activation effect.

[0041] In the present invention, the ratio of the mass of the WC powder after the surface pretreatment to the volume of the activation liquid is preferably 100-500 g:1L. In a specific embodiment, the ratio of the mass of the WC powder after the surface pretreatment to the volume of the activation liquid may be 100 g:1L, 150 g:1L, 200 g:1L, 250 g:1L, 300 g:1L, 350 g:1L, 400 g:1L, 450 g:1L or 500 g:1L.

[0042] In the present invention, when the ultrasonic assisted activation is performed, the ultrasonic power is preferably 300-400W, and in a specific embodiment, the ultrasonic power may be 300W, 350W or 400W; the ultrasonic time is preferably 20-30min, and in a specific embodiment, the ultrasonic time may be 20min, 25min or 30min; the ultrasonic frequency is preferably 40-60kHZ, and in a specific embodiment, the ultrasonic frequency may be 40kHZ, 45kHZ, 50kHZ, 55kHZ or 60kHZ. By using ultrasonic assistance, the gas generated in the activation reaction is discharged as quickly as possible to provide more space for the reaction; at the same time, the ultrasonic wave will produce an acoustic cavitation effect in the activation liquid. Under the action of ultrasonic waves, a local temporary negative pressure will be formed in certain areas of the activation liquid, and cavities or bubbles will be generated in the activation liquid. These bubbles are in an unstable state. When they are suddenly closed, shock waves will be generated, and high pressure and high temperature will be generated in a local micro-area, providing a favorable physical and chemical environment for the activation reaction.

[0043] In the present invention, the ultrasound-assisted activation treatment preferably further includes water washing, standing and drying.

[0044] The present invention also provides an activated WC powder, which is obtained by activating WC powder by the activation treatment method described in the above technical solution. The surface of the activated WC powder has gullies and pit structural defects. The presence of gullies and pit structural defects makes the WC powder have a larger surface energy, reduces the metal-ceramic interface contact angle, improves the wettability of WC and Co, and thus promotes the uniform growth of the Co coating on the powder surface. The structural defects can serve as nucleation centers to adsorb foreign substances to form bonds, so that the ceramic powder has catalytic activity.

[0045] The present invention also provides the use of the activated WC powder described in the above technical solution in preparing a WC composite material by chemical plating.

[0046] In the present invention, the WC composite material preferably includes an activated WC powder and a coating coated on the surface of the activated WC powder, and the coating may be at least one of a Co coating, a Ni coating and a Cu coating.

[0047] The present invention also provides a method for preparing WC-Co composite powder, comprising the following steps: mixing the activated WC powder described in the above technical solution with a Co-containing 2+ The WC-Co composite powder is obtained by mixing the WC-Co composite powder with a chemical plating solution, heating and ultrasonicating the WC powder in sequence to form a Co plating layer on the surface of the WC powder.

[0048] In the present invention, the composition of the chemical plating solution is preferably: 20-30 g / L of cobalt sulfate, 20-30 g / L of sodium hypophosphite, 40-60 g / L of sodium citrate, 20-30 g / L of boric acid, and the balance is water.

[0049] In the present invention, the content of cobalt sulfate in the chemical plating solution is preferably 20-30 g / L. In a specific embodiment, the content of cobalt sulfate in the chemical plating solution may be 20 g / L, 25 g / L or 30 g / L.

[0050] In the present invention, the content of sodium hypophosphite in the chemical plating solution is preferably 20-30 g / L. In a specific embodiment, the content of sodium hypophosphite in the chemical plating solution can be 20 g / L, 25 g / L or 30 g / L.

[0051] In the present invention, the content of sodium citrate in the chemical plating solution is preferably 40-60 g / L. In a specific embodiment, the content of sodium citrate in the chemical plating solution can be 40 g / L, 45 g / L, 50 g / L, 55 g / L or 60 g / L.

[0052] In the present invention, the content of boric acid in the chemical plating solution is preferably 20 to 30 g / L. In a specific embodiment, the content of boric acid in the chemical plating solution may be 20 g / L, 25 g / L or 30 g / L.

[0053] In the present invention, the ratio of the mass of the activated WC powder to the volume of the chemical plating solution is preferably 100-200 g:1L. In a specific embodiment, the ratio of the mass of the activated WC powder to the volume of the chemical plating solution can be 100 g:1L, 150 g:1L or 200 g:1L.

[0054] In the present invention, the pH value of the chemical plating solution is preferably 9 to 11. In a specific embodiment, the pH value of the chemical plating solution may be 9, 10 or 11. The chemical plating solution is adjusted to alkaline to prevent hydrogen ions from being precipitated during the chemical plating reaction and reduce the deposition rate of Co.

[0055] In the present invention, sodium hydroxide is preferably used for adjusting the pH value.

[0056] In the present invention, the heating temperature is preferably 75-85° C. In a specific embodiment, the heating temperature can be 75° C., 80° C. or 85° C. The present invention has no special requirements for the heating holding time, and the heating can be performed until bubbles are generated in the plating solution.

[0057] In the present invention, the power of the ultrasound is preferably 300-400W, and in a specific embodiment, the power of the ultrasound can be 300W, 350W or 400W; the frequency of the ultrasound is preferably 40-60kHZ, and in a specific embodiment, the frequency of the ultrasound can be 40kHZ, 45kHZ, 50kHZ, 55kHZ or 60kHZ; the temperature of the ultrasound is preferably 70-80°C, and in a specific embodiment, the temperature of the ultrasound can be 70°C, 75°C or 80°C. The present invention has no special requirements for the time of the ultrasound, and the ultrasound can be performed until no bubbles are generated. The present invention uses ultrasound to make the Co plating more uniform.

[0058] During the ultrasound process, the reaction occurs to Co 2+ +2H2PO 2- +2H2O→Co+2H2PO 2- +2H + +H2↑.

[0059] In the present invention, after the ultrasound, the obtained powder is preferably subjected to heat treatment. In the present invention, it is more preferred that the powder obtained by ultrasound is first washed and dried, and then heat treated. In the present invention, the heat treatment is preferably carried out in an inert environment, such as argon; the temperature of the heat treatment is preferably 200-220°C, and in a specific embodiment, the temperature of the heat treatment may be 200°C, 210°C or 220°C; the time of the heat treatment is preferably 5-7h, and in a specific embodiment, the time of the heat treatment may be 5h, 6h or 7h; the rate of heating to the temperature of the heat treatment is preferably 20°C / min.

[0060] In the present invention, the loading amount of Co in the WC-Co composite powder is preferably 2-4 wt%. In a specific embodiment, the loading amount of Co in the WC-Co composite powder may be 2 wt%, 3 wt% or 4 wt%.

[0061] In the present invention, the prepared WC-Co composite powder can be sintered to prepare WC cemented carbide.

[0062] In the present invention, the sintering method is preferably spark plasma sintering.

[0063] In the present invention, the vacuum degree of sintering is preferably >5Pa; the sintering pressure is preferably 50MPa; the sintering temperature is preferably 1400-1500°C, and in a specific embodiment, the sintering temperature can be 1400°C, 1450°C or 1500°C; the sintering holding time is preferably 5-10min, and in a specific embodiment, the sintering holding time is preferably 5min, 8min or 10min; the sintering heating rate is preferably 150°C / min.

[0064] The WC hard alloy obtained by the invention has a small grain size of 0.71-1.24 μm and a hardness of 2198.3-2708.4 HV.

[0065] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Any modification, equivalent replacement, improvement, etc. made to the implementation mode of the present invention based on the technical essence and general principles of the present invention without creative work should be within the scope of protection of the present invention.

[0066] Example 1

[0067] Preparation of activated WC powder

[0068] The WC powder was placed in ethanol for conventional ultrasonic cleaning, then washed three times with deionized water, allowed to stand for 12 hours, and then dried in a drying oven to obtain pretreated WC powder.

[0069] 65 vol% nitric acid, 40 vol% hydrofluoric acid, ammonium fluoride and deionized water are mixed to obtain an activation solution, wherein the concentration of 65 vol% nitric acid in the activation solution is 20 mL / L, the concentration of 40 vol% hydrofluoric acid is 40 mL / L, and the concentration of ammonium fluoride is 3 mL / L.

[0070] The activation solution was heated to 55°C in a water bath, the pretreated WC powder was kept at 55°C for 10 min, then added to the activation solution at a mass concentration of 250 g / L, ultrasonicated at 50 kHz ultrasonic frequency and 350 W power for 25 min, and washed with deionized water for 3 times to obtain activated WC powder.

[0071] Preparation of WC-Co composite powder

[0072] Cobalt sulfate, sodium hypophosphite, sodium citrate, boric acid and water are mixed and the pH value is adjusted to 10 with sodium hydroxide to obtain a chemical plating solution. The mass concentration of each substance in the chemical plating solution is 25 g / L of cobalt sulfate, 25 g / L of sodium hypophosphite, 50 g / L of sodium citrate and 25 g / L of boric acid.

[0073] The activated WC powder was added to the chemical plating solution at a mass concentration of 150g / L, heated to 80℃ in a water bath and kept warm for 10min. When bubbles were generated in the chemical plating solution, it was moved into the solution and ultrasonicated at 75℃, 50kHZ ultrasonic frequency and 350W power. When no bubbles were generated, it was centrifuged, washed with deionized water for 3 times, and dried in a drying oven. The dried composite powder was placed in an argon atmosphere, heated to 220℃ at 20℃ / min and kept warm for 6h to obtain a WC-Co composite powder, which was recorded as WC-3wt%Co composite powder.

[0074] Preparation of WC cemented carbide

[0075] The WC-3wt% Co composite powder was placed in a spark plasma sintering device, and the temperature was increased to 1450° C. at a rate of 150° C. / min and kept at that temperature for 5 minutes under a vacuum degree of 6 Pa and a sintering pressure of 50 MPa to obtain a WC cemented carbide.

[0076] Example 2

[0077] The concentration of 65 vol% nitric acid in the activation solution was 30 mL / L, and other conditions were the same as those in Example 1.

[0078] Example 3

[0079] The concentration of 65 vol% nitric acid in the activation solution was 40 mL / L, and other conditions were the same as in Example 1.

[0080] Example 4

[0081] The concentration of 65 vol% nitric acid in the activation solution was 50 mL / L, and other conditions were the same as in Example 1.

[0082] Example 5

[0083] The concentration of 65 vol% nitric acid in the activation solution was 60 mL / L, and other conditions were the same as those in Example 1.

[0084] Comparative Example 1

[0085] During the preparation of the WC-Co composite powder, no ultrasonic assistance was performed, and other conditions were the same as those in Example 1.

[0086] Comparative Example 2

[0087] WC powder was used to prepare WC-Co composite powder, and other conditions were the same as those in Example 1.

[0088] The activated WC powders of Examples 1 to 5 were scanned by electron microscope to obtain Figure 1 , Figure 1 1 to 5 in correspond to embodiments 1 to 5 respectively. Figure 1 It can be seen that the surface defects such as grooves on the surface of the WC powder obtained in Example 4 are relatively obvious. These parts will serve as nucleation centers to adsorb foreign substances to form bonds, making the ceramic powder catalytically active.

[0089] The WC-Co composite powders prepared in Examples 1 to 5 were scanned by electron microscope to obtain Figure 2 , Figure 2 1 to 5 in correspond to embodiments 1 to 5 respectively. Figure 2 It can be seen that the effect of Co-coated WC obtained in Example 4 is the most ideal, and the surface of the composite powder is round and smooth.

[0090] The WC hard alloys prepared in Examples 1 to 5 were scanned by electron microscope to obtain Figure 3 , Figure 3 1 to 5 in the examples 1 to 5 correspond to the examples 1 to 5 respectively. Figure 3 Calculation and analysis show that the average grain sizes of Examples 1 to 5 are 0.92 μm, 1.24 μm, 0.99 μm, 0.71 μm, and 0.91 μm, respectively, among which the WC cemented carbide obtained in Example 4 has the smallest grain size and the densest structure.

[0091] When preparing WC-Co composite powder, ultrasound is not used for assistance, which will lead to poor dispersion of Co particles generated in the chemical plating reaction, agglomeration of Co atoms, and inability to be uniformly adsorbed on the WC surface, thereby affecting the quality of the coating (Comparative Example 1). Directly using unactivated WC powder to prepare WC-Co composite powder, WC as a ceramic powder itself does not have self-catalytic activity, no catalytic center, and it is difficult for the surface to form a good bonding force with the metal coating, which will lead to failure of the chemical plating metal layer (Comparative Example 2).

[0092] The hardness of the WC cemented carbides prepared in Examples 1 to 5 was tested using a Vickers hardness tester. The results are shown in Table 1.

[0093] Table 1 Hardness of WC cemented carbide obtained in Examples 1 to 5 (±50HV0.2)

[0094] Example 1 Example 2 Example 3 Example 4 Example 5 Vickers hardness / HV0.2 2198.3 2375.5 2530.5 2708.4 2363.9

[0095] As can be seen from Table 1, the Vickers hardness of the WC cemented carbide obtained in Examples 1 to 5 shows a trend of first increasing and then decreasing. In the embodiments of the present invention, the highest hardness can reach 2708.4HV0.2. When the nitric acid concentration in the activation solution is increased to 60mL / L, the hardness of the obtained WC cemented carbide shows a downward trend. It shows that when the nitric acid concentration is too high, the activation effect of the WC powder is not ideal. When the nitric acid concentration is 50mL / L, the activated WC powder has the highest activity, and the effect of chemical Co coating is the most ideal. The grain size of the WC cemented carbide obtained by sintering is uniform and the smallest. And when the nitric acid concentration is increased to 60mL / L, the grain size of the WC cemented carbide obtained is significantly larger and uneven. It shows that the WC powder treated with an activation solution with a concentration of 65vol% nitric acid of 50mL / L, a concentration of 40vol% hydrofluoric acid of 40mL / L, and a concentration of 3g / L of ammonium fluoride has a higher activity.

[0096] The present invention improves the problems of high cost and unsatisfactory coating effect caused by the current use of precious metal activation, and the obtained activated WC powder has the advantages of high activity and compact coating effect. The present invention provides a formula of WC activation solution with high activation. During the activation process, nitric acid is used as a corrosive agent to etch defects such as gullies and pits on the surface of WC powder; hydrofluoric acid is used as a complexing agent to prevent the surface of WC powder from having body defects due to excessive nitric acid corrosion; ammonium fluoride provides fluoride ions during the activation process to prevent the solution from having insufficient complexing ability. After the WC powder is pretreated with high activation, a large number of uniform structural defects such as gullies and pits are generated on the surface of the powder, and lattice distortion and stress fields are generated around the defects, so that the activated WC powder has a larger surface energy, thereby reducing the contact angle of the metal-ceramic interface, improving the wettability between the WC powder and Co, reducing the metal nucleation work during the chemical plating process, and becoming the adsorption center of Co element microparticles, so that Co is more efficiently and uniformly attached to the surface of the WC powder, and chemical plating of Co is achieved. During the sintering process, the attached metal Co liquefies as a liquid phase and is evenly distributed between the activated WC particles, which helps to improve the toughness and strength of the alloy.

[0097] The activated WC powder obtained by the method provided by the present invention has high activity, and is more conducive to Co forming a uniform and dense Co coating layer on the surface of the WC powder during the chemical plating process. Compared with the traditional method of using precious metal activation, it is more environmentally friendly, green and efficient; at the same time, it also avoids the occurrence of continuous problems such as unsatisfactory Co coating effect due to low activity of WC powder, uneven distribution of bonding phase in the subsequent sintering process, and low mechanical properties of the alloy.

[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An activation solution, characterized in that: The activation solution is composed of: 20-60 mL / L of nitric acid with a concentration of 60-70 vol%, 30-50 mL / L of hydrofluoric acid with a concentration of 35-45 vol%, 2-4 g / L of ammonium fluoride, and the balance is water.

2. Use of the activation solution according to claim 1 in activating WC powder.

3. A WC powder activation treatment method, characterized in that: The following steps are involved: The WC powder is preheated, mixed with the activation solution of claim 1 at 50-60° C., and subjected to ultrasonic-assisted activation treatment to obtain activated WC powder.

4. The activation treatment method according to claim 3, characterized in that: The ratio of the mass of the WC powder to the volume of the activation solution is 100-500 g:1 L.

5. The activation treatment method according to claim 3 or 4, characterized in that: The conditions of the ultrasound-assisted activation treatment include: ultrasound power of 300-400W, ultrasound time of 20-30min, and ultrasound frequency of 40-60kHZ.

6. An activated WC powder obtained by activating WC powder by the activation treatment method according to any one of claims 3 to 5.

7. Use of the activated WC powder according to claim 6 in preparing WC composite materials by chemical plating.

8. A method for preparing WC-Co composite powder, characterized in that: The activated WC powder according to claim 6 is mixed with a Co-containing 2+ The WC-Co composite powder is obtained by mixing the WC-Co composite powder with a chemical plating solution, heating and ultrasonicating the WC powder in sequence to form a Co plating layer on the surface of the WC powder.

9. The preparation method according to claim 8, characterized in that: The ratio of the mass of the activated WC powder to the volume of the chemical plating solution is 100-200 g:1 L.

10. The preparation method according to claim 8, characterized in that: The chemical plating solution is composed of: 20-30 g / L cobalt sulfate, 20-30 g / L sodium hypophosphite, 40-60 g / L sodium citrate, 20-30 g / L boric acid, and the balance is water; The pH value of the chemical plating solution is 9-11.